The Role of Regulatory Bodies and Other Role-Players in the Promotion of Financial Inclusion in South Africa: Array - Chitimira, Howard; Ncube, Menelisi (Acta Universitatis Danubius. Juridica, 2020)
The promotion of financial inclusion is vital for the combating of financial exclusion in many countries, including South Africa. Nonetheless, most of the poor and low-income earners are still struggling to have access to basic financial products and financial services in South Africa. This status quo has been, inter alia, caused by several factors such as the lack of a specific statute for financial inclusion, the lack of a specific regulatory body to enforce that statute and the adoption of inadequate measures by the government and other role-players to effectively promote financial inclusion for the poor and low-income earners in South Africa. It is against this background that this article discusses the role of the government, regulatory bodies and other relevant role-players in the promotion of financial inclusion in South Africa. In this regard, the role of the South African Reserve Bank (SARB), the Banking Association South Africa (BASA), the National Consumer Tribunal (NCT), the National Credit Regulator (NCR), the National Treasury and the National Consumer Financial Education Committee (NCFEC), the Financial Sector Conduct Authority (FSCA) and the Prudential Authority (PA) is discussed. This is done to investigate whether these regulatory bodies and role-players have adopted adequate measures to robustly and consistently combat financial exclusion of the poor and low-income earners in South Africa.